Robot-assisted puncture versus conservative treatment for severe brainstem hemorrhage: clinical outcomes comparison with experience of 138 cases in a single medical center - Xingwang Sun; Junhao Zhu; Miao Lu; Zhibin Zhang; Cuiling Li; Rucai Zhan (World Journal of Emergency Surgery)
Abstract Introduction The application of robot-assisted surgical technology in treating brainstem hemorrhage has garnered increasing attention. Treatments such as stereotactic hematoma aspiration and neuroendoscopic surgery are becoming more prevalent in China. The aim of this study is to provide a detailed comparative analysis of the clinical effects of robot-assisted puncture technology versus traditional conservative treatment, offering a scientific basis for optimizing treatment plans and improving patient outcomes. Methods A retrospective observational study was conducted from January 2019 to December 2023 at a single neurosurgery center. A total of 138 patients with severe brainstem hemorrhage were included, with 103 in the conservative treatment group and 35 in the robot-assisted puncture group.ROSA robot-assisted brainstem hemorrhage drainage is a precise neurosurgical procedure involving pre-surgical evaluations and examinations, including cranial CT, to determine the hemorrhage’s location, extent, and severity. Baseline data was extracted from the hospital’s electronic medical record system, including demographics, medical history, and clinical characteristics. Statistical analysis was performed to compare outcomes between the two treatment groups. Results The baseline characteristics of the patients in both groups were similar, with no significant differences in age, gender, smoking history, alcohol consumption, or other relevant factors. The median stay time was longer in the robot-assisted group (21.0 days) compared to the conservative group (15.0 days), with a significant difference (p = 0.004). The median cost of hospitalization was also higher in the robot-assisted group (105231.0 yuan) compared to the conservative group (55221.5 yuan), with a significant difference (p < 0.001). The mortality rate of the robot assisted group was significantly lower than that of the conservative treatment group, and the difference was significant. Additionally, the robot-assisted group had a lower discharge hematoma volume and a trend towards better clinical outcomes, as measured by the Glasgow Coma Scale (GCS) and modified Rankin Scale (mRS) scores. Discussion The results suggest that robot-assisted puncture technology may offer improved clinical outcomes in patients with brainstem hemorrhage compared to traditional conservative treatment. The precision and accuracy of the ROSA robot may contribute to better hematoma drainage and reduced complications. While the cost of hospitalization was higher in the robot-assisted group, the potential for improved patient outcomes and reduced long-term healthcare costs should be considered when evaluating the cost-effectiveness of this treatment approach. Further research is needed to validate these findings in larger, multicenter studies and to explore the potential benefits of robot-assisted treatment in different subpopulations of patients with brainstem hemorrhage. Conclusion This study provides preliminary evidence that robot-assisted puncture technology may offer improved clinical outcomes in patients with brainstem hemorrhage compared to traditional conservative treatment. The precision and accuracy of the ROSA robot may contribute to better hematoma drainage and reduced complications, although the higher cost of hospitalization should be taken into account. Future research is needed to further validate these findings and explore the potential benefits of this innovative treatment approach.